Null controllability of viscous Hamilton-Jacobi equations - Porretta, Alessio; Zuazua, Enrique (Annales de l'Institut Henri Poincaré - Analyse Non Linéaire, 2012)
We study the problem of null controllability for viscous Hamilton-Jacobi equations in bounded domains of the Euclidean space in any space dimension and with controls localized in an arbitrary open nonempty subset of the domain where the equation holds. We prove the null controllability of the system in the sense that, every bounded (and in some cases uniformly continuous) initial datum can be driven to the null state in a sufficiently large time. The proof combines decay properties of the solutions of the uncontrolled system and local null controllability results for small data obtained by means of Carleman inequalities. We also show that there exists a waiting time so that the time of control needs to be large enough, as a function of the norm of the initial data, for the controllability property to hold. We give sharp asymptotic lower and upper bounds on this waiting time both as the size of the data tends to zero and infinity. These results also establish a limit on the growth of nonlinearities that can be controlled uniformly on a time independent of the initial data. (C) 2011 Elsevier Masson SAS. All rights reserved.
CRIS-Team WoS Importer:2019-12-13